The examination of the quality of life changes of patients with urolithiasis regarding different methods of treatment - Gvozdić, Branka; Milenković Petronić, Dragica; Ladjević, Nebojša; Vuksanović, Aleksandar; Durutović, Otaš (Vojnosanitetski pregled, 2021)
Background/Aim. Urolithiasis is one of the most common urological illnesses with a continual rise in incidence and prevalence in the population. Its pathogenesis is multi-factorial; hence, its consequences are serious problems that can significantly impact the quality of life of patients. In the last years, operational modes of urolithiasis treatment had undergone evolution changes towards minimally invasive treatment techniques aimed at improving its efficacy and patients' life quality. The aim of the study was to examine and evaluate the quality of life of the patients with urolithiasis depending on the applied treatment method. Methods. This research was designed as a panel study – a combination of a cross-sectional and cohort study. The sample included patients with urolithiasis treated with extracorporeal shock wave lithotripsy (ESWL) or ureteroscopic lithotripsy (Lithoclast). The research was carried during one year period and 100 respondents met the inclusion criteria. They were divided into two equal groups considering the applied method of the stone disintegration: the Lithoclast group (URSL) and the ESWL group. The instrument used for measuring the quality of life was Short Form (SF) 36 questionnaire. It was administrated to the patients immediately before the operation and one month after the operation. Results. The statistical analysis of the scores obtained preoperationally on the SF 36 questionnaire revealed the decrease in the quality of life of patients with urolithiasis in almost all dimensions of life. The statistically relevant difference in preoperative SF scores between the two groups of patients was not established except in the domain of the role of physical health and the domain of mental health. In the domain of the role of physical health, the Lithoclast group had a statistically significant higher score than the ESWL group, but in the domain of mental health, the ESWL group had a statistically significant higher score than the Lithoclast group. The postoperative statistical analysis of SF questionnaire and the examination of the impact of the treatment mode on the quality of life showed that the use of the Lithoclast method resulted in the much higher, statistically significant score at SF36 questionnaires regarding several life dimensions than the ESWL method. The application of the ESWL method even resulted in the decrease in the postoperational score for some life dimensions. Conclusion. The assessment of the quality of life is an adequate tool for the evaluation of treatment modes in the clinical practice. By using the SF 36 questionnaire in this study, we established that the ureteroscopic lithotripsy (the Lithoclast method) is a method that postoperatively results in much higher and statistically significant improvement of the quality of life of patients with urolithiasis in several health domains than the ESWL method.
Keywords: urolithiasis; lithotripsy; quality of life; surveys and questionnaires; methods; treatment outcome